2018
DOI: 10.1159/000489161
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Prurigo: An Unusual Presentation of Hodgkin Lymphoma

Abstract: Background: Prurigo nodularis is a condition of unknown origin defined by papulonodular eruption and intense pruritus. Hodgkin lymphoma often presents nonspecific initial symptoms. An association between systemic malignancy and cutaneous manifestations has long been documented. We report a case of prurigo nodularis as a first presentation of Hodgkin lymphoma. Case: A 35-year-old woman presented with a 2-year history of pruritus. Previously diagnosed with bedbugs, the pruritus persisted even after insect eradic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…Although IL-31 appears to have a role in pruritus in CTCL, there is conflicting evidence as to whether it plays a larger role in the pathogenesis of CTCL itself (56,58,59). However, of note, chronic prurigo has also been reported in cases of Hodgkin lymphoma (HL) (60), and a study in HL patients demonstrated elevated IL-31 in HL cells and in the immune cells infiltrating affected lymph nodes (61). Another recent study showed that plasma concentrations of IL-31 decreased in HL patients entering remission (62); taken together, these findings suggest that IL-31 may contribute to immune suppression in HL, and may indicate a similar role in CTCL.…”
Section: Cutaneous T-cell Lymphoma (Ctcl)mentioning
confidence: 99%
“…Although IL-31 appears to have a role in pruritus in CTCL, there is conflicting evidence as to whether it plays a larger role in the pathogenesis of CTCL itself (56,58,59). However, of note, chronic prurigo has also been reported in cases of Hodgkin lymphoma (HL) (60), and a study in HL patients demonstrated elevated IL-31 in HL cells and in the immune cells infiltrating affected lymph nodes (61). Another recent study showed that plasma concentrations of IL-31 decreased in HL patients entering remission (62); taken together, these findings suggest that IL-31 may contribute to immune suppression in HL, and may indicate a similar role in CTCL.…”
Section: Cutaneous T-cell Lymphoma (Ctcl)mentioning
confidence: 99%
“…Systemic and metabolic causes have been implicated in 38% to up to 50% of PN cases [25,26]. Some common systemic associations of PN are chronic renal failure, liver disease (chronic hepatitis B, primary biliary cholangitis, chronic autoimmune cholestatic hepatitis), HIV, thyroid disease, diabetes and malignances, specifically non-Hodgkin's lymphoma [3,4,[27][28][29][30][31][32][33][34][35][36]. A study (n = 16,925) by Larson et al found that pruritus was most strongly associated with cancers of the liver, skin, and hematopoietic system [37].…”
Section: Systemicmentioning
confidence: 99%
“…A study (n = 16,925) by Larson et al found that pruritus was most strongly associated with cancers of the liver, skin, and hematopoietic system [37]. Rarer malignancies that have been associated with PN are metastatic transitional cell carcinoma of the bladder and Hodgkin's lymphoma [30,38,39]. Other less commonly associated systemic causes are gout, iron-deficiency anemia, and celiac disease [26,32,40,41].…”
Section: Systemicmentioning
confidence: 99%
“…PN may initially present as grouped lesions but can disseminate to become more widespread 3 . Although the precise aetiology of PN remains unknown, it has been associated with comorbid dermatological conditions, such as atopic dermatitis (AD), 2,4–6 and with systemic inflammation and several systemic illnesses, including HIV, chronic renal failure, liver disease, thyroid disease and malignancy 2,6–15 . Compared with other chronic itch conditions, the itch of PN is among the most severe 16 …”
Section: Introductionmentioning
confidence: 99%